Blood biochemical parameters for assessment of COVID-19 in diabetic and non-diabetic subjects: a cross-sectional study. Issue 6 (3rd June 2022) - Malik, Syeda Umme Fahmida; Chowdhury, Parveen Afroz; Hakim, Al; Islam, Mohammad Shahidul; Alam, Md Jahangir; Azad, Abul Kalam
ABSTRACT: This study aims to identify blood biomarkers for rapidly predicting progression and severity assessment of COVID-19 in type 2 diabetic (DM) and non-DM (NDM) patients. Among 211 hospitalized patients suspected of COVID-19, 98 were confirmed COVID-19 by rRT-PCR. The COVID-19 positive group contained 58 DM and 40 NDM patients with total death 9 of which 7 were males and 6 were DM, indicating males and DM individuals as more susceptible to COVID-19. Blood biomarkers notably serum ferritin, CRP, D-dimer, ALT, troponin I, and Hb1Ac were significantly (p < 0.05) higher in COVID-19 patients. Ferritin and HbA1c levels were significantly (p < 0.05) higher in DM than NDM COVID-19 patients. The present study suggests that ferritin and HbA1c levels for DM patients, and ferritin, D-dimer, ALT for NDM patients could be routinely used as biomarkers for progression and severity assessment of COVID-19. CRP and Troponin-I could be the predictor only for poor prognosis of COVID-19.